The Effects of Bradykinin B1 Receptor Antagonism on the Myocardial and Vascular Consequences of Hypertension in SHR Rats - Deres, Laszlo; Eros, Krisztian; Horvath, Orsolya; Bencze, Noemi; Cseko, Csongor; Farkas, Sandor; Habon, Tamas; Toth, Kalman; Halmosi, Robert (Frontiers in Physiology, 2019)
It is known that non-steroidal anti-inflammatory drugs increase cardiovascular (CV) morbidity and mortality. In this study, we examined whether a novel anti-inflammatory drug, bradykinin B1 receptor antagonist (FGY-1153) treatment could influence the development of hypertensive organ damages in spontaneously hypertensive rats (SHR). SHRs were treated with low (FGY-120) or high dose FGY-1153 (FGY-400) and with placebo (Control) for 26 weeks. Wistar–Kyoto rats were used as aged-matched, normotensive controls (WKY). Body weight, food consumption and blood pressure were measured regularly. Echocardiography was performed at the beginning and at the end of the study. Light and electron microscopic analysis of heart and great vessels were performed, and the extent of fibrotic areas was measured. The phosphorylation state of prosurvival Akt-1/glycogen synthase kinase (GSK)-3β pathway and the activation of signaling factors playing part in the fibrotic processes – mitogen activated protein kinases (MAPKs), and TGF-β/Smad2 – were monitored using Western-blot. Body weight and food consumption as well as the elevated blood pressure in SHRs was not influenced by FGY-1153 treatment. However, both doses of FGY-1153 treatment decreased left ventricular (LV) hypertrophy and diastolic dysfunction in hypertensive animals. Moreover systolic LV function was also preserved in FGY-120 group. Increased intima-media thickness and interstitial fibrosis were not significantly diminished in great vessels. FGY-1153 treatment inhibited the expression of TGFβ and the phosphorylation of SMAD2 in the heart. Our results suggest that the tested novel anti-inflammatory compound has no deleterious effect on CV system, moreover it exerts moderate protective effect against the development of hypertensive cardiopathy.